P108 Publications Improve Wound Care Guideline Quality And Impact. (15th August 2013) - Bolton, L; Girolami, S; Corbett, L; Merkle, D
Abstract : Background: High quality evidence based (EB) wound care guidelines reduce costs of care and improve outcomes. They may help stem the growing burden of chronic wound care only if disseminated and used. Context: Publications supported development, quality and dissemination of EB wound care guidelines with content-validity (CV). Description of Best Practice: Multidisciplinary volunteer guideline developers from a global, non-profit wound care organisation with patient and wound-related specialty membership, used standardised evidence strength criteria and independently-rated CV Index as standardised recommendation strength to develop inclusive venous and pressure ulcer "Guidelines of Guidelines". Representatives of six North American societies collaboratively published research and educational opportunities identified by this unique guideline development process. Lessons for Guideline Developers, Adapters, Implementers, and/or Users: Publications accessible at the organisation website transparently described the guideline development process, a hallmark of guideline quality while enhancing awareness of the guidelines and EB CV recommendations worth implementing. Publications in multidisciplinary journals minimised sampling bias by inviting readership to complete online CV surveys. Publishing research and educational opportunities focused the field on EB research and education needs and fostered international cooperation, helping unify wound care across countries, settings and specialties. Medical school and university nursing and physical therapy programmes are disseminating core messages of EB CV wound care by using the guidelines, publications, patient brochures, algorithms and implementation tools to improve quality and consistency of care. Conclusion: Publications enhanced venous and pressure ulcer guideline development quality, awareness and use while unifying wound care and highlighting needed research and education initiatives.